Status and trends of the Canada Goose Branta canadensis in France - Fouque, Carol; Schricke, Vincent (Ornis Svecica, 2011)
An enquiry to determine the distribution and abundance of the Canada Goose Branta candensis in France was undertaken in 2008. Responses were received from 92 out of the 96 departments. Canada Geese were reported in 56 of the 92 departments, in 8 of which the species had only appeared after 2000. For half of the 56 departments, the species was observed only in summer. Canada Geese summered in 38 departments, numbering at least 4,250 birds. At least 6,000 birds are also thought to winter in France as of 2008/2009, when the species is more widespread. Winter numbers are increasing exponentially. In 5 departments, crop damage and public health issues have resulted in local management measures in the last 3 years (e.g. egg pricking and culling of adults). We discuss the need for further regulation and legislation in the light of these conflicts and hybridisation with other species.